2014
DOI: 10.1021/jp504018k
|View full text |Cite
|
Sign up to set email alerts
|

S-Oxygenation of Thiocarbamides V: Oxidation of Tetramethylthiourea by Chlorite in Slightly Acidic Media

Abstract: The reaction between tetramethylthiourea (TTTU) and slightly acidic chlorite has been studied. The reaction is much faster than comparable oxidations of the parent thiourea compound as well as other substituted thioureas. The stoichiometry of the reaction in excess oxidant showed a complete desulfurization of the thiocarbamide to yield the corresponding urea and sulfate: 2ClO2(-) + (Me2N)2C ═ S + H2O → (Me2N)2C ═ O + SO4(2-) + 2Cl(-) + 2H(+). The reaction mechanism is unique in that the most stable metabolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…23 Most strong to mild oxidants oxidize thiocarbamides to sulfate and their urea analogues. 1,12,13,24 Quantitative determination of sulfate was performed gravimetrically through BaSO 4 precipitation. Barium sulfate yields, taken from several experiments, showed that, on the average, 98.8% of the sulfur in DMTU was converted to sulfate.…”
Section: ■ Resultsmentioning
confidence: 99%
“…23 Most strong to mild oxidants oxidize thiocarbamides to sulfate and their urea analogues. 1,12,13,24 Quantitative determination of sulfate was performed gravimetrically through BaSO 4 precipitation. Barium sulfate yields, taken from several experiments, showed that, on the average, 98.8% of the sulfur in DMTU was converted to sulfate.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In this case only one metabolite was found, corresponding to 3-phenyl- N -[(4-piperidin-1-ylphenyl)carbamoyl]propanamide ( Figure S2 ). This derivative likely arises from sequential EthA reactions on the sulfur atom of the carbamothioyl moiety ( Chigwada et al., 2014 ). However, this last metabolite showed no effect on PyrG activity.…”
Section: Resultsmentioning
confidence: 99%
“…If at least one substituent R is a hydrogen atom, thioureas form relatively stable dioxides and trioxides. Tetraalkylthioureas, for example, tetramethylthiourea form in aqueous solutions relatively stable monoxides in the course of oxidation by bromine, bromate [50], chlorite [51], and hydrogen peroxide [52]; while formation of tetramethylthiourea dioxide and trioxide has not been observed at all. Indeed, higher oxides were earlier shown to be unavailable by means of oxidation of tetramethylthiourea by peroxides and alternative pathways of synthesis should be employed [53,54].…”
Section: Thiourea Oxides As the Sources Of Sosmentioning
confidence: 99%